Distribution and potential health risk of nitrate in centralized groundwater sources of Wanbei Plain, Central China - Yunhu Hu (IWA Publishing, 2021)
Centralized groundwater sources are the main source for drinking, domestic, industry, and agriculture in Central China. Thirty-five centralized groundwater sources were selected to determine the concentration and distribution characterization of nitrate in Wanbei Plain, Anhui Province. Meanwhile, the health risk assessment model recommended by USEPA was used to evaluate the potential health risk for adults and children. The results showed that the average concentration of nitrate in the pore water is lower than that of karst water, which may be attributed to the thinner thickness of loose sediments for karst water. The nitrate in groundwater mainly originates from chemical fertilizers, industrial and domestic waste. The health risk of nitrate to children through drinking water intake and skin contact was significantly higher than that of adults, which was explained by their being more sensitive receptors and facing higher health risks than adults. The non-carcinogenic risk of nitrate in all samples was within the acceptable range. The results also indicated drinking water control is the main way to reduce nitrate health risk. Nevertheless, there is an urgent need to take measures to strengthen groundwater management, improve groundwater quality, and reduce nitrate health risk. HIGHLIGHTS The average concentration of nitrate in the pore groundwater is lower than that of karst.; Children are more sensitive receptors and face higher health risks than adults.; Drinking water control is the main way to reduce nitrate health risk.; All risks are within the acceptable range.; Protective measures should be taken to avoid the nitrate pollution in groundwater and prevent its concentration from increasing.;